(untitled) (Colombia Medica, 2013)
We report a case of a 47-year-old male, who was referred to the clinical hepatology services at Pablo Tobón Uribe Hospital for evaluation of a jaundice syndrome. After undergoing several exams, we diagnosed hepatic hydatidosis and the patient was treated with albendazole; however, after five months of uninterrupted treatment the patient again consulted and his liver test showed marked hepatocellular damage. This time, the patient was diagnosed with drug-induced liver injury due to albendazole, based on information from the clinical record, history of drug consumption, clinical and laboratory tests improved after discontinuing the medication and after discarding other possible causes; this diagnosis was supported by the CIOMS/RUCAM scale, which showed a “likely” correlation between hepatocellular damage and drug toxicity etiology.